Experimental Investigation of Air Humidity Impact on Natural Convection Cooling of Electronic Circuits - Marcin Kaluza; Marcin Lebioda (IEEE Access)
Elevated temperature is the main cause of electronic circuits failures, thus a proper thermal management is indispensable. The heat from operating circuits is dissipated by conduction, radiation and convection. Several papers related to the impact of air relative humidity on natural convection cooling of electronic circuits, based on theoretical analysis, suggesting such impact, were published so far. The goal of the presented research was to investigate the problem experimentally. A dedicated measurement setup composed of a cubic enclosure placed inside a climatic chamber was built. A bipolar transistor placed inside the enclosure was used as a controlled heat source. To assess the cooling efficiency, the transistor junction temperature was maintained constant using a custom build controller circuit and the power dissipated in the device was measured. Additionally, the surface temperature of the transistor was measured using a thermographic camera and a MWIR optical fiber. The measurements were repeated for different temperature and relative humidity combinations. Based on obtained measurement results and their analysis, backed-up by simulations, it was found that air relative humidity has no impact on electronic circuits cooling efficiency in the natural convection scenario. The theoretical background of the results was also explained.